2019
DOI: 10.1371/journal.pone.0213362
|View full text |Cite
|
Sign up to set email alerts
|

Delays in arrival and treatment in emergency departments: Women, children and non-trauma consultations the most at risk in humanitarian settings

Abstract: Introduction Delays in arrival and treatment at health facilities lead to negative health outcomes. Individual and external factors could be associated with these delays. This study aimed to assess common factors associated with arrival and treatment delays in the emergency departments (ED) of three hospitals in humanitarian settings. Methodology This was a cross-sectional study based on routine data collected from three MSF-supported hospitals in Afghanistan, Haiti and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 45 publications
1
19
1
3
Order By: Relevance
“… 9 This delayed presentation may be compounded by low health literacy, lack of pre hospital care, belief in traditional healers and quality medical facilities inaccessible to the less privileged. 13 , 21 Over half the mortalities in low-resource settings may be addressed by improved emergency care systems. 22 Our study has identified that encouraging timely presentation to healthcare, availability of pre hospital care and swift transfer to tertiary care may mitigate some deaths.…”
Section: Discussionmentioning
confidence: 99%
“… 9 This delayed presentation may be compounded by low health literacy, lack of pre hospital care, belief in traditional healers and quality medical facilities inaccessible to the less privileged. 13 , 21 Over half the mortalities in low-resource settings may be addressed by improved emergency care systems. 22 Our study has identified that encouraging timely presentation to healthcare, availability of pre hospital care and swift transfer to tertiary care may mitigate some deaths.…”
Section: Discussionmentioning
confidence: 99%
“…5 This again increases the likelihood that they will be exposed to communicable diseases. In addition, social norms prevalent in many humanitarian settings dictate that women and girls are the last to receive medical attention when they become ill. 6 These norms could prevent women and girls-particularly those who are already stigmatised, such as IDPs and refugees, members of certain ethnic or racial groups or those of different sexual orientationsfrom accessing testing and timely treatment for COVID-19. Furthermore, testing may not be available for some displaced populations, as illustrated in Bangladesh, where testing facilities are limited to the capital, Dhaka, which is 400 km away from the world's largest refugee camp in Cox's Bazar.…”
Section: Healthmentioning
confidence: 99%
“… Source: [ 26 , 29 , 30 , 33 , 36 , 47 , 49 , 59 , 60 , 61 , 62 , 131 , 136 , 137 ]. Note: each pathway can have multiple health impacts (not shown).…”
Section: Figurementioning
confidence: 99%
“… Source based on [ 4 , 13 , 14 , 16 , 29 , 30 , 35 , 47 , 48 , 50 , 52 , 54 , 137 , 139 , 152 , 157 , 159 , 160 , 161 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation